(3GdGSfGO GdJLGQjI h GdGadGS (B/s - (3TeS GdOjf, Yajas ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2010)
(3GdESfGO GdJLGQjI, SfO GdSMH, SfO GdCeQ, GdTjc, SGFQ GdESfGO GdJLGQjIs
Keywords: (3GdGadGSs; (3GdChQGb GdJLGQjIs; (3GdSfOGJs